Potential use of vanadium compounds on therapeutics - Barrio, Daniel Alejandro (2010)
Vanadium is a trace element present in practically all cells in plants and animals. While the essentiality of vanadium for human beings remains to be well established, vanadium has become an increasingly important environmental metal. Vanadium compounds exert a variety of biological activities and responses. At pharmacological doses, vanadium compounds display relevant biological actions such as insulin and growth factor mimetic or enhancing effects, as well as osteogenic and cardioprotective activity. On the other hand, depending on the nature of compounds and their concentrations, toxicological actions and adverse side effects may also be shown. Nevertheless, the toxic effects may be useful to develop new antitumoral drugs. In this review, the authors summarize current knowledge and new advances on in vitro and in vivo effects of inorganic and organically-chelated vanadium compounds. The effects of vanadium derivatives on some cellular signaling pathways related to different diseases are compiled. In particular, the pathways relevant to the insulin mimetic, osteogenic, cadioprotective and antitumoral actions of vanadium compounds have been comprehensively reviewed. The knowledge of these intracellular signaling pathways may facilitate the rational design of new vanadium compounds with promising therapeutic applications as well as the understanding of secondary side effects derived from the use of vanadium as a therapeutic agent.